LITERATURE REVIEW : PENGARUH KERJA SHIFT TERHADAP GEJALA GASTROESOPHAGEAL REFLUX DISEASE (GERD) PADA PEKERJA - ,, Andriyeni; Br Perangin-Angin, Fanny Gabriella (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
Background: Shift work, particularly during nighttime hours, disrupts circadian rhythm regulation of gastric acid secretion and lower esophageal sphincter function. This physiological dysregulation may increase susceptibility to Gastroesophageal Reflux Disease (GERD). Several studies have consistently reported a higher prevalence of GERD symptoms among shift workers compared with those working regular daytime schedules. Method: A literature review was conducted through PubMed, Google Scholar, and Garuda databases using the keywords “shift work,” “GERD,” and “questionnaire,” covering publications from 2015 to 2025. Eight articles met the inclusion criteria, which involved active workers, cross-sectional study design, and GERD symptom measurement using standardized questionnaires. Result: Most studies demonstrated a higher prevalence of GERD symptoms among shift workers (23–40%) compared with non-shift workers. Increased risk was associated with prolonged exposure to night shifts and poor sleep quality. A meta-analysis indicated that shift work significantly increased the likelihood of GERD (Odds Ratio 1.53; 95% CI 1.33–1.77). Conclusion: Shift work shows a significant association with increased GERD symptoms through circadian disruption, psychological stress, and irregular sleep patterns. Preventive workplace strategies, including healthier shift scheduling and health promotion interventions, are needed to reduce GERD risk among shift workers.